Adjuvant treatment and outcome of stage III melanoma patients: results of a multicenter real-world German Dermatologic Cooperative Oncology Group (DeCOG) study - Lodde, Georg Christian; Hassel, Jessica C.; Wulfken, Lena Margarethe; Meier, Friedegund; Mohr, Peter; Kähler, Katharina C.; Hauschild, Axel; Schilling, Bastian; Loquai, Carmen; Berking, Carola; Hüning, Svea; Eckardt, Julia; et al. (European journal of cancer, 2023)
Purpose - Clinical trials demonstrated significantly improved recurrence-free survival (RFS) of melanoma patients receiving adjuvant treatment. As data from controlled trials are based on selected populations, we investigated adjuvantly treated stage III melanoma patients under real-world conditions. - Patients and methods - In a prior multicenter cohort study, stage III-IV melanoma patients were analysed for their choice of adjuvant therapy. In this follow-up study, we examined RFS, overall and melanoma-specific survival (MSS) and response to the subsequent treatment of 589 stage III patients (232 BRAF-mutated) receiving adjuvant PD-1 inhibitors (PD1; n = 479) or targeted therapy (TT; n = 110). - Results - The median follow-up of the total cohort was 25.7 months. The main reason for premature discontinuation of adjuvant therapy was disease progression in PD1- (28.8%, n = 138/479) and adverse events in TT-treated patients (28.2%, n = 31/110). Among BRAF-mutated patients, RFS at 24 months was 49% (95% CI 40.6-59.0%) for PD1- and 67% (95% CI 58-77%) for TT-treated patients. The risk of recurrence was higher for BRAF-mutated PD1 than TT (hazard ratio 1.99; 95% CI 1.34-2.96; hazard ratio adjusted for age, sex and tumour stage, 2.21; 95% CI 1.48-3.30). Twenty-four months MSS was 87% (95% CI 81.0-94.1) for PD1 and 92% (95% CI 86.6-97.0) for TT. Response to subsequent systemic treatment for unresectable disease was 22% for all PD1- and 16% for TT-treated patients. - Conclusions - PD1-treated patients had more and earlier recurrences than TT patients. In BRAF-mutated patients, adjuvant TT might prevent early recurrences more effectively than PD1 treatment. Management of recurrence despite adjuvant treatment is challenging, with low response to current therapeutic options.